Determinants of psychotherapists’ attitudes to online psychotherapy - Rutkowska, Emilia; Furmańska, Joanna; Lane, Hakan; Marques, Cristiana C.; Martins, Maria João; Sahar, Najam us; Meixner, Johannes; Tullio, Valeria; Argo, Antonina; Bermeo Barros, David Marcelo (Frontiers in Psychiatry, 2023)
Abstract Introduction: Online psychotherapy is a form of work that is becoming more and more popular. Public health problems, such as COVID-19, forced mental health professionals and patients to incorporate new methodologies such as the use of electronic media and internet to provide follow-up, treatment and also supervision. The aim of this study was to investigate which factors shape the therapists’ attitudes towards online psychotherapy during a pandemic taking into account: (1) attitudes towards the COVID-19 pandemic (fear of contagion, pandemic fatigue, etc.), (2) personal characteristics of the psychotherapists (age, gender, feeling of efficacy, anxiety, depression, etc.), and (3) characteristics of the psychotherapeutic practice (guideline procedure, client age group, professional experience, etc.). Material and Methods: Study participants were 177 psychotherapists from four European countries: Poland (n=48), Germany (n=44), Sweden (n=49), and Portugal (n=36). Data were collected by means of an individual online survey through the original questionnaire and the standardized scales: A modified version of the Attitudes towards Psychological Online Interventions Scale (APOI), Fear of Contagion by COVID-19 Scale (FCS COVID-19), Pandemic Fatigue Scale (PFS), Hospital Anxiety and Depression Scale (HADS), Social Support Questionnaire (F-SozU K-14), and the The Sense of Efficiency Test (SET). Results: Determinants that impacted psychotherapists’ attitudes toward online therapy were: COVID-19 belief in prevention - keeping distance and hand disinfection, pandemic behavioral fatigue, previous online therapy experience (including voice call), working with youth and adults. Our study showed that belief in the sense of prevention in the form of taking care of hand disinfection before the session, pandemic behavioral fatigue and experience in working with adults were significant predictors of negative attitudes of therapists towards online psychological interventions. On the other hand, belief in the sense of prevention in the form of keeping distance during the session had a positive effect on general attitudes towards therapy conducted via the internet. Discussion: The online therapy boom during the COVID-19 pandemic has spawned a powerful tool for psychotherapists. More research in this area and training of psychotherapists are needed for online psychological interventions to become an effective therapy format that is accepted by patients and therapists alike.